Biopoéticas para las biopolíticas: El pensamiento literario latinoamericano ante la cuestión animal - Yelin, Julieta (Latin America Research Commons, 2020)
This book addresses the state of research that links recent Latin American literature and literary criticism to the current of posthumanist thought. To do this, it tests the notion of biopoetics, a reading device that aims to identify and analyze the procedures through which literary writing approaches the living. The hypothesis that supports the chapters is that Latin American literary thought, in its productive facet and in its critical facet, dialogues with the current horizon of reflection on the politics of life, and that it does so through experiments in which Bodies and affections are not only organizing centers of narratives but also lenses, ethical and political perspectives on the present. Thus, the volume offers a transdisciplinary theoretical panorama and a set of critical interventions that feed each other: in the overlap between language and life, an object is cut out, Latin American biopoetic writing, which in turn makes theory think.